Development of cell-based assay for detecting replication-competent adeno-associated virus by qPCR - Aishwarya Shevade; John S. Reeves; Hanne Bak; Andrew D. Tustian (Molecular Therapy: Methods & Clinical Development)
Recombinant, non-replicative adeno-associated virus (AAV) containing a therapeutic gene of interest (GOI) is widely used as a vector for gene therapy. One way to manufacture AAV is through triple-transfection of HEK293 cells, with plasmids containing the (1) GOI, (2) replication (rep2) and capsid (cap) sequences, and (3) adenovirus helper sequences. During the manufacturing of AAV, replication-competent AAV (rcAAV) could theoretically be generated via homologous and non-homologous recombination events. rcAAV contaminants could lead to reduced efficacy, or an adverse immunogenic response. Therefore, testing is required by regulatory agencies. However, there is a paucity of literature on this critical assay. Here, we have developed a sensitive, cell-based assay for detection of rcAAV in AAV8 preparations. After transducing HEK293 cells over three rounds with AAV8 in the presence of helper adenovirus 5, we performed qPCR to detect the presence of rcAAV using the rep2 gene as a marker. The optimized assay is performed at a 2 mL scale, minimizes the generation of false-positive results, and achieves a reportable result of 1 rcAAV per 106 vector genomes. The same approach for rcAAV method development can be expanded to all other AAV serotypes, providing means for substantially improving process development and product safety.